Optimization of applied voltages for on-chip concentration of DNA using nanoslit. (7th November 2017) - Azuma, Naoki; Itoh, Shintaro; Fukuzawa, Kenji; Zhang, Hedong
Abstract: On-chip sample concentration is an effective pretreatment to improve the detection sensitivity of lab-on-a-chip devices for biochemical analysis. In a previous study, we successfully achieved DNA sample concentration using a nanoslit fabricated in the microchannel of a device designed for DNA size separation. The nanoslit was a channel with a depth smaller than the diameter of a random coil-shaped DNA molecule. The concentration was achieved using the entropy trap at the boundary between the microchannel and the nanoslit. DNA molecules migrating toward the nanoslit owing to electrophoresis were trapped in front of the nanoslit and the concentration was enhanced over time. In this study, we successfully maximize the molecular concentration by optimizing the applied voltage for electrophoresis and verifying the effect of temperature. In addition, we propose a model formula that predicts the molecular concentration, the validity of which is confirmed through comparison with experimental results.